ESG principles for increasing the efficiency of the oil and gas complex - S. A. Gorshkov (Вестник университета)
The research purpose is   to determine the possibility of   applying ESG principles in   the process of   forming development prospects for modern Russian oil and gas organisations from the perspective of  an ecosystem approach. The subject of   the study is  tools for increasing efficiency. The methods of  content analysis, synthesis and verbal modelling have been used. It   is shown that the orientation of  the country’s oil and gas complex to  ensure the sustainability of   social and corporate governance while preserving the ecology of   the environment helps to  increase the efficiency of   the complex in  the future. In   this case, it   will receive competitive advantages which can be  appreciated by   investors who organise the attraction of   financial and information resources as  well as   human, material and energy resources. The novelty of   the results obtained lies in   the substantiation of   the approach that is   founded on a   combination of  such categories as  ESG principles, sustainable development, ecosystem approach, and strategic management. The results of  the study prove the feasibility of   applying the ESG principles as  tools which ensure the sustainable development of   modern Russian oil and gas organisations based on  the ecosystem approach in  the process of   searching solutions to   increase the efficiency of  the core activities. The approach contributes to  the formation of a   specific ecosystem where within the framework of  its development strategy the efficiency of   both a   network of   technologically related organisations and organisations that produce complementary goods and provide infrastructure services to   the entire oil and gas complex is   guaranteed.